Assessment of mitogen-activated protein kinases as therapeutic targets for the treatment of babesiosis and theileriosis - MUTLU, ÖZAL (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2020)
The Piroplasmida order comprises parasitic protozoa including the Theileria and Babesia species that are transmitted by vector ticks and can cause severe diseases in domestic and wild animals. Because of limited therapies and available drug resistance, the discovery of new, effective, and safer drugs for veterinary use is important. Mitogen-activated protein kinases (MAPK) are a group of serine-threonine protein kinases found in diverse species, including animals and protozoa that conduct vital cellular functions. Therefore, they have been at the centre of drug design studies for many years. Computer-aided structure-based drug design is a fast and effective way in drug discovery efforts to identify candidate compounds. In this study, we conducted comparative sequence analysis of MAPK proteins from the Theileria (T. annulata, T. parva., T. orientalis, and T. equi) and Babesia species (B. bigemina, B. microti, and B. bovis). Three-dimensional protein structures from relevant species (T. annulata and B. bovis) were modelled and compounds were screened for interaction. Results showed that the inhibitors designed for human use could also be potent against Prioplasmida MAPKs. Furthermore, the structural differences between Prioplasmida and mammalian MAPKs could be a way for researchers to better instigate selective drug design.
Keywords: Mitogen-activated protein kinase; computer-aided drug design; theileriosis; babesiosis; PARASITE PLASMODIUM-FALCIPARUM; TOXOPLASMA-GONDII; MOLECULAR-CLONING; MAP KINASES; INHIBITOR; ANNULATA